TECHNOLOGY AND ITS EFFECT ON THE FLEXIBILITY OF AUDITORIUM'S DESIGN (Journal of Engineering, 2003)
The technical development in scientific fields, has an effective influence in developing the possibilities of auditorium design, erection and performance. In the recent years, there was a great demand for flexible spaces, which could accommoder e different acting performance and would be economical too.Therefore technical efforts and facilities can be great help in providing flexibility's in geometrical relations, space configuration, material treatment and surface finishes of multi purpose halls. This research emphasis the importance of technical possibilities in both mechanical and acoustical sides for providing flexibility's in acoustical performance in auditorium by:1 Theoretical side discussinga Technical possibilities in multi purpose halls,b Main acoustical charseters and parameters, which are important for the evaluation of acoustical performance of multi purpose hallsPractical side; uradying an example which in the national theater in Baghdad as study case, and calculating the acoustical parameters mathematically and discussing its technical possibilities and then giving acoustical and technical advice for developing its functional and acoustical performance.